EFEKTIVITAS PROGRAM PARENTING DALAM MENINGKATKAN KESADARAN PENTINGNYA KOLABORASI PENDIDIKAN ANTARA SEKOLAH DAN ORANG TUA - Muthiarah, Imas (Jurnal Anak Bangsa, 2024)
This research aims to evaluate the role of parenting education in increasing parents' knowledge and awareness about early childhood care at PAUD Kober Ar Ridhoimas. The research method used is qualitative with a case study approach, involving interviews, observation and documentation to collect data. The main findings show that the parenting program implemented at PAUD Kober Ar Ridho is effective in increasing parents' awareness about educational collaboration. This program has succeeded in increasing communication between parents and teachers, parent participation in school activities, and support for learning at home. In addition, strengthening collaboration between parents and schools through parenting activities, effective communication, involvement as volunteers, and participation in decision making shows a positive impact on parental involvement in children's education. However, factors such as limited parental time, access to technology, and coordination between various parties pose challenges to the success of the program. Suggestions for improvement include increasing technological support, adapting program materials, facilitating parental involvement, and regular evaluation. This research provides valuable insight into ways to increase the effectiveness of parenting programs and educational collaboration at the PAUD level